Model Negara Kekuasaan: Orde Baru dalam Tinjauan Pemikiran Hobbes dan Niccolo Machiavelli - Oktaviani, Jusmalia; Pramadya, Teguh Puja (Indonesian Perspective, 2019)
This study explains the socio-political conditions of government in the New Order era and revisits the situation at that time from the perspective of Thomas Hobbes and Niccolo Machiavelli. This is based on the desire of some parties who want to return Indonesia back to the New Order era which is considered by some people to provide political and economic stability. This paper argues that the New Order and the state power model as described by Hobbes and Machiavelli thinking placed the unity of the state as the core idea, which made the country stable and did not experience horizontal conflicts. But with globalization, the rapid development of technology and the power of social media, making Indonesia as an authoritarian state as before would be difficult, if not impossible to do. It is important to study the thoughts of these two figures because both Machiavelli and Hobbes attach great importance to the unity and integrity of the state, and avoid the state from breaking up due to conflict and war.